Antibody-Dependent Cell-Mediated Cytotoxicity to Hemagglutinin of Influenza A Viruses After Influenza Vaccination in Humans. (18th May 2016) - Zhong, Weimin; Liu, Feng; Wilson, Jason R.; Holiday, Crystal; Li, Zhu-Nan; Bai, Yaohui; Tzeng, Wen-Pin; Stevens, James; York, Ian A.; Levine, Min Z.
Abstract : We used an improved ADCC assay to investigate HA-ADCC antibody responses in human sera following either seasonal or avian influenza vaccination. Our results suggest that detection of both neutralizing and non-neutralizing antibodies may better reflect protective capacity of HA-specific antibodies induced by avian influenza vaccines. Abstract: Background. Detection of neutralizing antibodies (nAbs) to influenza A virus hemagglutinin (HA) antigens by conventional serological assays is currently the main immune correlate of protection for influenza vaccines However, current prepandemic avian influenza vaccines are poorly immunogenic in inducing nAbs despite considerable protection conferred. Recent studies show that Ab-dependent cell-mediated cytotoxicity (ADCC) to HA antigens are readily detectable in the sera of healthy individuals and patients with influenza infection. Methods. Virus neutralization and ADCC activities of serum samples from individuals who received either seasonal or a stock-piled H5N1 avian influenza vaccine were evaluated by hemagglutination inhibition assay, microneutralization assay, and an improved ADCC natural killer (NK) cell activation assay. Results. Immunization with inactivated seasonal influenza vaccine led to strong expansion of both nAbs and ADCC-mediating antibodies (adccAbs) to H3 antigen of the vaccine virus in 24 postvaccination human sera. In sharp contrast, 18 individuals vaccinated with the adjuvanted H5N1 avian influenza vaccine mounted H5-specific antibodies with strong ADCC activities despite moderate virus neutralization capacity. Strength of HA-specific ADCC activities is largely associated with the titers of HA-binding antibodies and not with the fine antigenic specificity of anti-HA nAbs. Conclusions. Detection of both nAbs and adccAbs may better reflect protective capacity of HA-specific antibodies induced by avian influenza vaccines.